Evaluation of Secure Mobile and Clinical Communication Solution (SMaCCS) across acute and community practice settings. Issue 1 (28th September 2020) - Spina, Sean P; Atwood, Kristin M; Loewen, Peter
Abstract : Aims: Clinicians struggle to provide information to each other that supports safe patient transitions, especially across acute and community care jurisdictions. They need flexible communication tools to improve care coordination. Island Health introduced a Secure Mobile and Clinical Communication Solution (SMaCCS) to address these challenges in 2018. In this study we evaluated the SMaCCS system to understand the (1) volume and flow of healthcare communication, (2) degree of adoption and accessibility of the system and (3) user experience. Methods: This was a prospective, cross-sectional, observational study. Island Health Information Management/Information Technology (IMIT) selected Vocera Collaboration Suite as the secure messaging platform. We invited healthcare providers in various roles in the hospital and community to use SMaCCS for their daily communications and system and survey data were collected between February and August 2018. System data and survey data were used to determine outcomes. Results: A Sankey diagram represents the volume and flow of communication. A total of 2542 messages were sent and 79% of conversations included more than a single message. Eighty-one per cent of participants agreed that using a secure communication tool made them feel more comfortable sharing patient information. Most users (65%) perceived that the application was a useful method for transmitting simple information. Conclusion: However, our study showed that different occupational roles require different frequencies and volumes of communication and there are numerous barriers to adoption that must be addressed before secure messaging can be an effective, ubiquitous method of clinical communication.